Internalisasi Living Hadis tentang Pelaksanaan Shalat pada Waktunya dalam Kehidupan Religius Mahasiswa Pascasarjana Pendidikan Agama Islam - Ansorul Alim; Amri Saputra; David Ricardo; Marhumah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study analyzes the internalization, interpretation, and practice of the Living Hadith “Afdhalul a’māl aṣ-ṣalāh fī waqtihā” (performing prayer on time) among postgraduate students of Islamic Religious Education (PAI) at UIN Sunan Kalijaga, and identifies the influencing factors. Using a qualitative approach with a Living Hadith design, data were collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman model. The hadith is understood not merely as ritual duty but as a moral value of discipline and time management, shaping a religious habitus. This appears in practices such as pausing classes for prayer, scheduling studies around prayer times, and using prayer for emotional regulation. Yet, gaps persist between ideals and practice due to overlapping schedules and cultural tendencies to delay prayer. The study concludes that the vitality of Living Hadith depends on both individual awareness and institutional support aligning academic systems with spiritual values.